Engineering Vascularized Islet Macroencapsulation Devices: An in vitro Platform to Study Oxygen Transport in Perfused Immobilized Pancreatic Beta Cell Cultures - S. A., Fernandez; K. S., Champion; L., Danielczak; M., Gasparrini; S., Paraskevas; R. L., Leask; C. A., Hoesli (Frontiers in Bioengineering and Biotechnology, 2022)
Islet encapsulation devices serve to deliver pancreatic beta cells to type 1 diabetic patients without the need for chronic immunosuppression. However, clinical translation is hampered by mass transport limitations causing graft hypoxia. This is exacerbated in devices relying only on passive diffusion for oxygenation. Here, we describe the application of a cylindrical in vitro perfusion system to study oxygen effects on islet-like clusters immobilized in alginate hydrogel. Mouse insulinoma 6 islet-like clusters were generated using microwell plates and characterized with respect to size distribution, viability, and oxygen consumption rate to determine an appropriate seeding density for perfusion studies. Immobilized clusters were perfused through a central channel at different oxygen tensions. Analysis of histological staining indicated the distribution of viable clusters was severely limited to near the perfusion channel at low oxygen tensions, while the distribution was broadest at normoxia. The results agreed with a 3D computational model designed to simulate the oxygen distribution within the perfusion device. Further simulations were generated to predict device performance with human islets under in vitro and in vivo conditions. The combination of experimental and computational findings suggest that a multichannel perfusion strategy could support in vivo viability and function of a therapeutic islet dose.